2022
DOI: 10.1021/acsami.2c11715
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization of 3D Printed Porous Tantalum Using a Vancomycin–Carboxymethyl Chitosan Composite Coating to Improve Osteogenesis and Antibiofilm Properties

Abstract: 3D-printed porous tantalum scaffold has been increasingly used in arthroplasty due to its bone-matching elastic modulus and good osteoinductive ability. However, the lack of antibacterial ability makes it difficult for tantalum to prevent the occurrence and development of periprosthetic joint infection. The difficulty and high cost of curing periprosthetic joint infection (PJI) and revision surgery limit the further clinical application of tantalum. Therefore, we fabricated vancomycin-loaded porous tantalum sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Previously, we successfully grafted antituberculosis drugs (isoniazid and rifampicin) using polydopamine and vancomycin using chitosan on the surface of 3D-printed porous Ta . The results indicated that sustained-released antibacterial drugs from both composite scaffolds exhibited excellent bactericidal effects on S. aureus , providing new approaches for bone tuberculosis (Figure F) and periprosthetic joint infection treatment (Figure G) . Some researchers prepared Ta oxide layers containing phosphorus and calcium on the surfaces of porous Ta scaffolds using microarc oxidation technology to mimic a bony chemical composition and tissue morphology; zinc nanoparticles were coated on the oxide film using magnetron sputtering technology for antibacterial functionalization (Figure H) .…”
Section: Antibacterial Functionalization Of Ta Scaffoldsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we successfully grafted antituberculosis drugs (isoniazid and rifampicin) using polydopamine and vancomycin using chitosan on the surface of 3D-printed porous Ta . The results indicated that sustained-released antibacterial drugs from both composite scaffolds exhibited excellent bactericidal effects on S. aureus , providing new approaches for bone tuberculosis (Figure F) and periprosthetic joint infection treatment (Figure G) . Some researchers prepared Ta oxide layers containing phosphorus and calcium on the surfaces of porous Ta scaffolds using microarc oxidation technology to mimic a bony chemical composition and tissue morphology; zinc nanoparticles were coated on the oxide film using magnetron sputtering technology for antibacterial functionalization (Figure H) .…”
Section: Antibacterial Functionalization Of Ta Scaffoldsmentioning
confidence: 99%
“…(G) Biofunctionalization of porous Ta via a vancomycin–carboxymethyl chitosan coating. Adapted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Antibacterial Functionalization Of Ta Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18 ] Carboxymethyl chitosan (CMC), a water‐soluble derivative of chitosan, contains functional amino and carboxyl groups and exhibits good biocompatibility, hydrophilicity, and biodegradability. [ 19 ] In addition, CMC can chelate calcium ions to promote osteogenic activity. [ 20 ] However, simple CMC hydrogels suffer from swelling in water and lacks the necessary organic components of bone tissue.…”
Section: Introductionmentioning
confidence: 99%